2019
DOI: 10.1016/j.ejmech.2019.03.056
|View full text |Cite
|
Sign up to set email alerts
|

High affinity CXCR4 inhibitors generated by linking low affinity peptides

Abstract: G-protein coupled receptors (GPCRs) are implicated in many diseases and attractive targets for drug discovery. Peptide fragments derived from protein ligands of GPCRs are commonly used as probes of GPCR function and as leads for drug development. However, these peptide fragments lack the structural integrity of their parent full-length protein ligands and often show low receptor affinity, which limits their research and therapeutic values. It remains a challenge to efficiently generate high affinity peptide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…This method 54,57,76,84,86,88,117,121,126,129,132,134,136,160,161,171,252 is based on the theory that if a residue has a significant contribution ligand binding, the overall binding affinity might be remarkably changed when it is mutated into another amino acid (e.g., alanine). Therefore, we could perform site-directed mutagenesis to residues in both orthosteric and allosteric sites and to see whether the ligand binding is influenced in both the Fig.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…This method 54,57,76,84,86,88,117,121,126,129,132,134,136,160,161,171,252 is based on the theory that if a residue has a significant contribution ligand binding, the overall binding affinity might be remarkably changed when it is mutated into another amino acid (e.g., alanine). Therefore, we could perform site-directed mutagenesis to residues in both orthosteric and allosteric sites and to see whether the ligand binding is influenced in both the Fig.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…64,65 The wise application of a combination of chemical, molecular modeling, mutagenesis, and biological approaches has led to the continuous discovery and development of more potent cyclic, bivalent, and multivalent analogs (Table 2). 52,53,56,57,59,60,6269 The molecular modeling of CXCR4 dimer–synthetic ligand interactions based on the crystal structure of CXCR4 has demonstrated that synthetic dimeric ligands are capable of interacting with the CXCR4 dimeric structure by allowing the essential amino acid residues to interact with binding or signaling pockets of CXCR4 molecules. The use of different linkers, including polyethylene glycol, poly(L-proline), or Ahx, could allow the maintenance of an appropriate distance between the two binding sites of the ligands, consistent with that of CXCR4 dimers.…”
Section: Cxcr4-targeted Peptides That Function As Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
“…The use of different linkers, including polyethylene glycol, poly(L-proline), or Ahx, could allow the maintenance of an appropriate distance between the two binding sites of the ligands, consistent with that of CXCR4 dimers. 6668 This part of research will surely be expanded in the future, not only to develop drug leads, but also to elucidate how the lead ligands interact with the amino acid residues of CXCR4.…”
Section: Cxcr4-targeted Peptides That Function As Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations